PENETAPAN HARGA DAN NILAI TAMBAH GULA AREN DI MUARA BULIAN KABUPATEN BATANGHARI - Rosyani; Maros Framita, Rebeca; Alamsyah, Zulkifli (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2021)
This study aims to (1) find out the general description of palm sugar agro-industry in Muara Bulian, (2) analyze the determination of the price of palm sugar to be marketed and (3) analyze the added value of palm sugar agro-industry. The data analysis method used is a quantitative descriptive method using the help table analysis of the added value analysis of the Hayami method and using the Cost Plus method Pricing From these calculations will be known the amount of added value per production process and the profits received by industry and the optimum price to be marketed. The added value is then used to measure agroindustry productivity by using value added ratios. The results showed that (1) the agroindustry of palm sugar in Bulian estuary still produces traditionally and is developed in a descending manner. Print sugar agro-industry consists of 63 active craftsmen who produce sugar almost every day and 6 of them have produced ant sugar. Until now there is only one craftsman who still produces ant sugar, (2) based on the results of the Cost Plus Pricing analysis, the optimal printed sugar mark-up is IDR 5,000 / kg which will provide a selling price of IDR 18,683.63 / kg, while the Mark the optimal ant sugar up is IDR 10,000 / kg up to IDR 18,000 / kg which will provide a selling price of IDR 37,617 / kg up to IDR 45,617.85 / kg, (3) processing palm sugar into ant sugar will produce added value and profit which is higher than the processing of palm sugar into printed sugar because the ratio of added value of ant sugar is higher than that of printed sugar.